2022
DOI: 10.1371/journal.pone.0279286
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of PARP inhibitors in malignancies: A systematic review

Abstract: Objectives Poly (ADP-ribose) polymerase inhibitor (PARPi) have become a mainstay for the treatment of BRCA-mutant malignancies. PARPis are likely to be more effective but also bring an increase in costs. Thus, we aimed at evaluating the cost effectiveness of PARPis in the treatment of malignancies. Methods Studies of cost effectiveness of PARPis were searched from PubMed, Web of Science, and Cochrane Library. Key information was extracted from the identified studies and reviewed. Quality of the included stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(226 reference statements)
0
1
0
Order By: Relevance
“…A systematic review conducted by Haiying et al reviewed 25 papers (17 on ovarian cancers, 3 on pancreatic cancer, 3 on prostate cancer and 2 on breast cancer) on the cost-effectiveness of the use of PARPI. PARPIs that were involved in the study included olaparib, rucaparib, talazoparin and niraparib [ 106 ]. The majority of the studies demonstrated the cost-effectiveness of olaparib in the setting of newly diagnosed patients after first-line platinum-based therapy; however, cost-effectiveness was reduced in patients with platinum-sensitive recurrences.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…A systematic review conducted by Haiying et al reviewed 25 papers (17 on ovarian cancers, 3 on pancreatic cancer, 3 on prostate cancer and 2 on breast cancer) on the cost-effectiveness of the use of PARPI. PARPIs that were involved in the study included olaparib, rucaparib, talazoparin and niraparib [ 106 ]. The majority of the studies demonstrated the cost-effectiveness of olaparib in the setting of newly diagnosed patients after first-line platinum-based therapy; however, cost-effectiveness was reduced in patients with platinum-sensitive recurrences.…”
Section: Cost-effectivenessmentioning
confidence: 99%